2019
DOI: 10.1105/tpc.19.00714
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Quality Control Mechanisms in the ER and TGN Determine Subcellular Dynamics and Salt-Stress Tolerance Function of KORRIGAN1

Abstract: Among many glycoproteins within the plant secretory system, KORRIGAN1 (KOR1), a membrane-anchored endo-b-1,4glucanase involved in cellulose biosynthesis, provides a link between N-glycosylation, cell wall biosynthesis, and abiotic stress tolerance. After insertion into the endoplasmic reticulum, KOR1 cycles between the trans-Golgi network (TGN) and the plasma membrane (PM). From the TGN, the protein is targeted to growing cell plates during cell division. These processes are governed by multiple sequence motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 83 publications
(154 reference statements)
0
23
0
Order By: Relevance
“…Especially glycoproteins that depend on complex-type N-glycan modification seem to be compromised in Arabidopsis and rice gntI mutants, leading to a reduced cellulose content ( Kang et al, 2008 ; Fanata et al, 2013 ). Moreover, impairments in complex N-glycosylation affect the function and stability of KORRIGAN1, a glycoprotein with eight mostly complex N-glycans ( Kang et al, 2008 ; Liebminger et al, 2013 ; Rips et al, 2014 ; Nagashima et al, 2020 ; Kaulfürst-Soboll et al, 2021 ), which plays an important role for cellulose synthesis at the PM ( Nicol et al, 1998 ; Sato et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially glycoproteins that depend on complex-type N-glycan modification seem to be compromised in Arabidopsis and rice gntI mutants, leading to a reduced cellulose content ( Kang et al, 2008 ; Fanata et al, 2013 ). Moreover, impairments in complex N-glycosylation affect the function and stability of KORRIGAN1, a glycoprotein with eight mostly complex N-glycans ( Kang et al, 2008 ; Liebminger et al, 2013 ; Rips et al, 2014 ; Nagashima et al, 2020 ; Kaulfürst-Soboll et al, 2021 ), which plays an important role for cellulose synthesis at the PM ( Nicol et al, 1998 ; Sato et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when there are mutations in the catalytic extracellular domain, KOR1 accumulates at the tonoplast (TP), likely for subsequent degradation (Rips et al, 2014). Nagashima et al (2020) investigated the multiple determinants for the subcellular localization of KOR1 and the related physiological significance in plant growth and stress tolerance. Nagashima et al (2020) identified a C-terminal Pro-rich motif (termed the P-motif) that retains KOR1 in the TGN network/PM cycle.…”
mentioning
confidence: 99%
“…Nagashima et al (2020) investigated the multiple determinants for the subcellular localization of KOR1 and the related physiological significance in plant growth and stress tolerance. Nagashima et al (2020) identified a C-terminal Pro-rich motif (termed the P-motif) that retains KOR1 in the TGN network/PM cycle. To explore the development of KOR1, the authors created an estradiol-inducible KOR1 reporter construct with a tandem fluorescent timer (tdFT) protein to induce de novo synthesis and monitor newly synthesized and aged KOR1 en route to its final destination(s).…”
mentioning
confidence: 99%
See 2 more Smart Citations